Dye–polyoxometalate coordination polymer as a photo-driven electron pump for photocatalytic radical coupling reactions. Issue 95 (16th November 2021) - Ming, Zheng; Zhang, Tiexin; Tian, Wenming; Li, Jianing; Liu, Zhenhui; Liu, Renhai; Liu, Zhongmin; Duan, Chunying
Abstract : Coordination polymer containing triphenylamine and polyoxometalate photoinduced long-lived charge-separation pairs, which unidirectionally pumped multiple electrons from external electron donors to acceptors, furnishing value-added radical couplings. Abstract : To alleviate diffusion-limited photoinduced electron transfer (PET) in solution, a triphenylamine-derived dye and a Keggin polyoxometalate-type electron relay were coupled into a coordination polymer to photoinduce long-lived charge-separation pairs with enough reductive/oxidative potential to pump multiple electrons unidirectionally from external electron donors to acceptors, thus furnishing photocatalytic radical couplings to afford value-added α-amino C–H arylation products.